MANAJEMEN PEMBELAJARAN DALAM PEMBINAAN AKHLAK SISWA DI MADRASAH TSANAWIYAH AL-MAIDAR PANDAN - Lis Yulianti Siregar (IAIN Padangsidimpuan, 2021)
This research conducted in Madrasah Tsanawiyah Al-Maidar Pandan. The results of the study are as follows: The character of morality in Madrasah Tsanawiyah Al-Maidar Pandan consists of three stages, namely: planning, implementation and evaluation of learning in moral character building. Planning is done by preparing the instructional administration early in the school year. Implementation of moral coaching using several strategies, methods in the delivery of learning materials. Other efforts are made in the following ways: a) Familiarize 5 S (Smile, Sapa, Greetings, Sharing, Polite Eid), b) Read the Qur'an on Friday, c) Good relationship with parents. d) Through exemplary, advice or motivation and education through punishment. e) Good communication to students. f) Creating a religious atmosphere. Evaluation used to measure the success of moral coaching students is the assessment in writing in the form of report cards and also the assessment in the form of words through the three domains of cognitive, affective and psychomotor domains